2023
DOI: 10.18632/aging.204807
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the predictive function of cuproptosis-related gene FDX1 in clear cell renal carcinoma using qRT-PCR and western blotting

Abstract: Background: Cuproptosis is a novel cell death mechanism, and FDX1 is a key gene associated with cuproptosis. However, it is unclear whether FDX1 has prognostic and immunotherapeutic value for clear cell renal carcinoma (ccRCC). Methods: Data on FDX1 expression in ccRCC were extracted from various databases and validated using qRT-PCR and western blotting. Moreover, the survival prognosis, clinical features, methylation, and biological functions of FDX1 were evaluated, and the tumor immune dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…FDX1 is a protein involved in cuproptosis localized to the mitochondrial membrane [ 50 ]. Recent studies have identified FDX1 as a regulator of protein lipoylation involved in cellular cuproptosis [ 51 , 52 ]. Additionally, studies have identified FDX1 as a direct target of ES which enhances a distinct form of Cu-dependent cell death [ 53 ].…”
Section: Cuproptosis In Dmmentioning
confidence: 99%
“…FDX1 is a protein involved in cuproptosis localized to the mitochondrial membrane [ 50 ]. Recent studies have identified FDX1 as a regulator of protein lipoylation involved in cellular cuproptosis [ 51 , 52 ]. Additionally, studies have identified FDX1 as a direct target of ES which enhances a distinct form of Cu-dependent cell death [ 53 ].…”
Section: Cuproptosis In Dmmentioning
confidence: 99%